Characterization of polyvinylidene fluoride (PVDF) hollow fiber membrane on different lithium chloride (LICL) loading for carbon dioxide (CO2) removal - Nor Atikah, Mohd (2015)
In this study, hollow fiber membranes (PVDF – LiCl) were studied as one of the efficient alternatives for carbon dioxide removal. The membranes were prepared via phase inversion method by using the wet spinning process. An aqueous dimethylacetamide (DMAc) solution was used as a solvent. The experimental was conducted to investigate the effect of different lithium chloride (LiCl) concentration on the membrane properties and membrane structure. The prepared fibers were characterized in term of gas permeation, critical water entry pressure (CEPw), water contact angle and morphology analysis. Results of gas permeation test showed that with increasing of LiCl concentration, the pore size of membrane became smaller and increased in the effective surface porosity. The cross-section, inner surface and outer surface of membranes were examined via scanning electron microscopy (SEM). It gave a result that by addition of LiCl, membrane structure change from finger-like to sponge-like layer, which resulted in a high wetting pressure and N2 permeation rates. Membrane with 5% LiCl gave higher hydrophobicity than plain PVDF and 3% LiCl membrane. It was suggested that higher hydrophobicity of PVDF membrane may be an effective way for long-term operating performance of CO2 removal. Therefore, these results concluded that small pore size, high surface porosity and high wetting resistance are the important factors in producing an efficient membrane for CO2 removal.